Adsorption of Methyl Green Dye onto Bamboo in Batch and Continuous System - Adnan Atshan, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Adsorption techniques are widely used to remove certain classes of pollutants from waters, especially those that are not easily biodegradable. Dyes represent one of the problematic groups. The removal of methyl green from waste water using bamboo was studied in batch and continuous system. In batch system equilibrium time and adsorption isotherm was studied at different concentrations (5, 10, 15, 20, 25 and 30 ppm) and 50 mg weight of adsorbent. Langmuir and Freundlich equations were applied for adsorption isotherm data. Langmiur equation was fitted better than Freundlich equation (R2=0.984 for Langmuir equation).The maximum percentage dye removal obtained 79.4% and adsorption capacity was 15.5 mg/g. For continuous system the breakthrough curve was studied at different bed depths (1, 2 and 4 cm), different concentrations (5 and 10 ppm), and different flow rates (5 and 10 ml/min).